Nuclear Medicine in Poland, the Role of Radiation Protection in Nuclear Medicine - Królicki, Leszek (Contemporary Oncology/Współczesna Onkologia, 2002)
Nuclear medicine is a separate medical discipline, which cumulates different diagnostic and therapeutic procedures. It progress in Poland is very limited. Because the number of different clinical procedures is growing the role of radiation protection in nuclear medicine must be specific and is specially important.